Profile of an occupation – organ builder - Schambeck, Arne [Verfasser] (My University, 2022)
"No two organs are the same since each one is individually made for the architectural space in which it is intended to ring out. Organ builders are specialists in a trade which builds on centuries of experience and combines traditional craft techniques with the latest technologies. Organ builder is clearly one of the musical instrument-making training occupations which attracts considerable interest. In a survey conducted by our BWP newsletter, a clear majority said they wished to learn more about this occupation." (author's abstract; BIBB-Doku)
Keywords: 370; Orgelbauer; Berufsbild; Tätigkeitsfelder